(untitled) (مجلة إحالات, 2026)
The Algerian folk song is one of the most important manifestations of the expression of Algerian social life, which made it live with great acceptance among the Algerian people, as it embodies various important aspects of their life, whether religious, cultural or political, and this is what made it have a great impact on the same Algerian recipient. In this research paper, we seek to extract the set of political and religious patterns behind popular songs of an Andalusian nature, which rely on aesthetic rhetorical language, and to reveal the dark side of the reality of the Algerian people through the song “Ya Hasret Alaikum Ya Al-Dunya” by Kamal Masoudi, relying on the cultural approach.